The Earliest villages in Iron Age Iberia (800–400 BC): a view from Cerro de San Vicente (Salamanca, Spain) - Antonio Blanco-González; Cristina Alario García; Carlos Macarro Alcalde (Documenta Praehistorica, 2017)
The onset of the Iron Age underwent manifold disruptions. The emergence of long-lasting nucleated villages in Iberia c. 900/800 BC best encapsulates such profound changes. This paper draws on the results of excavations over the last few decades at a fortified tell-like settlement in central Iberia: Cerro de San Vicente (Spain). The article focuses on formation dynamics in earth architecture to understand the role of cultural choices in the genesis of these sites. The occurrence of sophisticated lifestyles and novel cultural expressions in this village (avant-garde devices such as a drain pipe, unprecedented building techniques, exotic imports and alien practices) suggests the plausible role of inter-regional migration in their adoption. The appraisal of intra-site spatial arrangements sheds fresh light upon the diachronic social trajectories of these agrarian communities, from a seemingly egalitarian organisation to an increasingly ranked one.